An Accidental Intestinal Myiasis Caused by Cochliomyia macellaria - P. P. Jayawardana; T. C. Yahathugoda (Hindawi Limited, 2021)
Intestinal myiasis is recognized as pseudomyiasis or accidental myiasis caused by dipteran fly larvae transmitted to humans via contaminated food or water. A case of intestinal myiasis acquired via contaminated food is reported in this case study. The patient is a 4-year-old boy who had frequent episodes of crampy abdominal pain and diarrhoea and the passage of many live worms at each time. As the child had the habit of eating ripe guava from his garden, the infection source was suggested as ripe guava, and the possibility was explored. All larvae collected from faeces and fruit were morphologically similar, and it has been identified as Cochliomyia macellaria. The treatment with several antihelmintics failed, and the recovery was achieved with a simple measure of abstinence from eating guava that came from his garden.